The Tarpaulin: From the Lens of the Young Meranaw - Fajardo, Loreta (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2022)
The practice of displaying tarpaulins among Meranaws traces its history to the times when gongs were sounded and people would celebrate for the victories of Sultans after conquering places and for union of individuals in marriage. This practice has earned for Marawi city to be called as City of Streamers in the 70s and 80s. With advancement of technology, the form gas evolved, thus, we have the tarpaulins.